2014
DOI: 10.1073/pnas.1319738111
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of naïve human embryonic stem cells

Abstract: The naïve pluripotent state has been shown in mice to lead to broad and more robust developmental potential relative to primed mouse epiblast cells. The human naïve ES cell state has eluded derivation without the use of transgenes, and forced expression of OCT4, KLF4, and KLF2 allows maintenance of human cells in a naïve state [Hanna J, et al. (2010) Proc Natl Acad Sci USA 107 (20):9222-9227]. We describe two routes to generate nontransgenic naïve human ES cells (hESCs). The first is by reverse toggling of pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
458
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 423 publications
(481 citation statements)
references
References 25 publications
21
458
2
Order By: Relevance
“…Several studies comparing naïve and primed pluripotent stem cells have indicated that the two types of cells exhibit different molecular and functional properties, including colony morphologies, single-cell passage abilities [7,8], dependent signaling pathways [6,9,10], pluripotent gene expression profiles, and, most important, mouse embryo integration capacity to generate cross-species chimeras [7,11,12]. Previous studies have also suggested that human primed iPSCs and mouse EpiSCs can be converted to the naïve ground state via chemical manipulation or the overexpression of specific transcription factors [12][13][14][15][16][17]. Recently, several groups have further modified culture conditions to maintain human ESCs or iPSCs in the naïve ground state [12,13,15,18].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies comparing naïve and primed pluripotent stem cells have indicated that the two types of cells exhibit different molecular and functional properties, including colony morphologies, single-cell passage abilities [7,8], dependent signaling pathways [6,9,10], pluripotent gene expression profiles, and, most important, mouse embryo integration capacity to generate cross-species chimeras [7,11,12]. Previous studies have also suggested that human primed iPSCs and mouse EpiSCs can be converted to the naïve ground state via chemical manipulation or the overexpression of specific transcription factors [12][13][14][15][16][17]. Recently, several groups have further modified culture conditions to maintain human ESCs or iPSCs in the naïve ground state [12,13,15,18].…”
Section: Introductionmentioning
confidence: 99%
“…For example, since human ESCs bear numerous similarities to EpiSCs [5,6], our model predicts that ectopic Cdx2 would not induce expression of TSC-like cell genes in human ESCs in the conditions we tested here. Recently, totipotent or naïve pluripotent stem cell lines have been derived from both humans and mice [56][57][58][59][60]. In several cases, these cell lines have been shown to contribute to extraembryonic lineages in chimeras.…”
Section: Figmentioning
confidence: 99%
“…These conditions also make ES cell derivation possible from normally recalcitrant mouse strains [33] and rat embryos [34], and most recently a variant of 2i has been used to derive naive human ES cells [15][16][17]. In 2i conditions, ES cells are also heterogeneous and include a significant fraction of cells that can be prospectively isolated based on the expression of the extraembryonic transcription factor Hhex [35] (figure 1b).…”
Section: Totipotent Cellsmentioning
confidence: 99%